PHAEOCHROMOCYTOMA IN A PATIENT WITH SUSPECTED BIRT-HOGG-DUBÉ SYNDROME: AN INCIDENTAL OR COMPOSITE RELATIONSHIP? - Momoh, Rabiu; Alkundi, Alamin; Nash , Marcus (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND A rare case of phaeochromocytoma in a 57-year-old female patient with a provisional clinical diagnosis of Birt-Hogg- Dubé (BHD) syndrome is presented. Whether this is an incidental finding or whether a causative or composite relationship between these two entities remains to be fully described. As much as we are aware, our case would be the second of such association to be described in literature. CASE The patient’s hospital record was reviewed after consent was obtained. Bilateral renal cysts and a right adrenal lesion were first identified in the patient at age 48 from abdominal CT studies done for her recurrent bilateral flank pain. To date, two percutaneous drainages of cysts on the right kidney were done to relieve pain. Following assessment of patient at a tertiary hospital’s genetics clinic at age 52, a provisional diagnosis of Birt-Hogg-Dube (BHD) syndrome was made for her bilateral renal cysts and notable skin lesions. Her CT chest study did not reveal lung cysts. Genetic mutation studies for FLHN, FH, MET, SDHB and VHL genes were negative. The patient’s right adrenal lesion was under surveillance and eventually required right adrenalectomy for newly developed recurrent episodic hypertension at age 54. Histology showed paraganglioma-like appearance, a 2% Ki-67 index and a negative SDHB staining. The patient’s daughter was also diagnosed with bilateral renal cysts and recurrent spontaneous pneumothoraces and a provisional diagnosis of DHB syndrome variant was also made for her. CONCLUSION Further research work into the above rarely-described clinical association needs to be done.